2007
DOI: 10.1111/j.1574-6968.2007.00858.x
|View full text |Cite
|
Sign up to set email alerts
|

Laccases produced by lichens of the orderPeltigerales

Abstract: 'Large' and 'small' fractions of laccase were found in the thalli of lichens Solorina crocea and Peltigera aphthosa. In both lichens, 'large', possibly dimeric, laccases were determined as 175 and 165 kDa (based on the gel filtration data), and 'small' ones were 76 and 97 kDa (according to sodium dodecyl sulfate-polyacrylamide gel electrophoresis data), respectively. By their substrate specificity, pH optima, and thermostability, they were typical laccases. The fractions of 'small' laccases of 45 kDa from S. c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(12 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…40 and 80 kDa), similar to the behavior of lichen laccases (Lisov et al, 2007;Laufer et al, 2009). Also in crude extracts of thalli from two further Peltigerales lichens monomeric and dimeric laccases (88 & 158 kDa for C. flaccidum) as well as peroxidase (39 & 82 kDa as well as 36 & 47 kDa for C. flaccidum and P. canina, respectively) were electrophoretically identified (data not shown).…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…40 and 80 kDa), similar to the behavior of lichen laccases (Lisov et al, 2007;Laufer et al, 2009). Also in crude extracts of thalli from two further Peltigerales lichens monomeric and dimeric laccases (88 & 158 kDa for C. flaccidum) as well as peroxidase (39 & 82 kDa as well as 36 & 47 kDa for C. flaccidum and P. canina, respectively) were electrophoretically identified (data not shown).…”
Section: Discussionmentioning
confidence: 59%
“…(Kirk et al, 2008). Only limited information is available on the oxidoreductases from lichenized fungi, but recently it has been shown that some species can display high activities of the multi-copper oxidases laccase and tyrosinase (Laufer et al, 2006a(Laufer et al, ,b, 2009Zavarzina and Zavarzin, 2006;Lisov et al, 2007).…”
Section: Introductionmentioning
confidence: 98%
“…Other well studied laccase‐producing ascomycetes include the non‐pathogenic species from the genera Aspergillus , Curvularia , Penicillium , Trichoderma, and Bothryosphaeria . Laccases have been studied in lichens and lichenized ascomycetes from the genera Solorina , Peltigera, Lobaria, Collema, Nephroma, Psuedocyphellaria, and Sticta . Studies have shown that laccases purified and characterized from lichens present typical fungal laccase biochemical behavior (pH and temperature profile, molecular weights and thermal stabilities).…”
Section: A Traditional Strategies For Laccase Production and Improvementioning
confidence: 99%
“…57,64 Laccases have been studied in lichens and lichenized ascomycetes from the genera Solorina, Peltigera, Lobaria, Collema, Nephroma, Psuedocyphellaria, and Sticta. [65][66][67][68] Studies have shown that laccases purified and characterized from lichens present typical fungal laccase biochemical behavior (pH and temperature profile, molecular weights and thermal stabilities). Additionally, yellow or white laccases (lacking the characteristic blue color originating from the type 1 Cu) have been detected in some lichens.…”
Section: Alternative Sources Of Native Laccasesmentioning
confidence: 99%
“…One of the advantages of laccases is that they reach not require hydrogen peroxide for substrate oxidation and otherwise, they use oxygen as a non-limiting electron acceptor (Michizoe et al, 2005). Laccases are ubiquitous enzymes present in higher plants, bacteria, fungi, insects and lichens (Riva 2006;Lisov et al, 2007). Due to their sophisticated redox potential as compared to the natural world or bacterial laccases, fungal ones are implicated in several biotechnological applications (Brijwani et al, 2010).…”
Section: Introductionmentioning
confidence: 99%